The Modulor : a Harmonious Measure to the Human Scale Universally applicable to Architecture and Mechanics - Le Corbusier, 1887-1965 (Birkhäuser, 2000)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> A fundamental work in the history of architecture - as a beautiful facsimile edition.